MENINGKATKAN KECERDASAN EMOSI DAN INTELIGENSI SISWA MELALUI PENINGKATAN KUALITAS PEMBELAJARAN PENDIDIKAN JASMANI - Nurkholis Nurkholis (Universitas Negeri Malang, 2016)
Ameliorating the EQ and IQ of Primary School students through quality enhancement of physical-exercise education. This classroom action research (CAR) was aimed to ameliorate the EQ and IQ of Primary School students through physical-exercise education. 38 sixth graders of Sekolah Dasar Negeri (Public Primary School) Lidah Kulon II Surabaya participated in this study. Analyses of curriculum, relevant literature, observation results, and test results were conducted. Results of the analyses show that the quality of physical-exercise teaching and learning did not significantly improve the students' intelligence. However, the use of games in the teaching-learning process allowed for the improvement of the students' EQ.